The encyclopedia of world ballet - Snodgrass, Mary Ellen (Lanham Rowman & Littlefield, 2015)
In the Encyclopedia of World Ballet, Mary Ellen Snodgrass surveys the emergence of ballet from ancient Asian models to the present, providing overviews of rhythmic movement as a subject of art, photography, and cinema. Entries in this volume reveal the nature and purpose of ballet, detailing specifics about leaders in classic design and style; influential costumers and companies; and trends in technique, partnering, variation, and liturgical execution. This reference covers choreographers, composers, costumers, dance companies, dancers, productions, set designers, techniques, and terminology
Preface -- Acknowledgements -- Introduction -- Chronology -- Encyclopedia -- Bibliography -- Index -- About the author
Includes bibliographical references (pages 329-335) and index
Keywords: Ballet -- Encyclopedias